Laparoscopic cholecystectomy in situs inversus totalis (Revista Argentina de Cirugía, 2026)
Situs inversus totalis (SIT) is defined as the presence in “mirror-image” of internal organs’ normal positioning and occurs in 6,500 to 25,000 live births. This autosomal recessive condition is associated with congenital anomalies. In patients with SIT and symptomatic cholelithiasis (SCL), laparoscopic cholecystectomy (LC) is the standard of care. We report the case of a 30-year-old female patient with dextrocardia and pain in the left hypochondriac region (LHC). A diagnosis of SCL in DIT was made and the patient underwent LC using the French “mirror” technique. The operative time was 90 minutes, there were no complications and the patient was discharged on postoperative day 1. Laparoscopic cholecystectomy in SIT could be performed safely and effectively with the appropriate technical precautions to address the difficulties of this anatomic variant.
Keywords: laparoscopic cholecystectomy; situs inversus totalis; French technique